Comprehensive study of the readiness for change and tolerance for uncertainty in police officers of Rapid Response Corps with different levels of resilience - S. S. Boychuk (Law and Safety)
A comprehensive analysis of "readiness for change" and "tolerance for uncertainty" phenomena in the field of psychological science is presented. Theoretical investigations have shown that the outlined concepts have been widely considered in the works of domestic and foreign scientists. The aim of the work was to empirically study of the readiness for change in the relationship with the components of tolerance for uncertainty in police officers of the special police units with different levels of resilience.